We Are Not Alone: Examining the Impact of a Teen Diabetes Day Camp - Heidi Blaylock; Eddie Hill; Carter Leuba; Christina Aguilar; Carla Cox (Behavioral Sciences)
Type 1 diabetes (T1D) is a chronic disease that influences all health aspects. The self-determination theory (SDT) suggests that three psychological needs of competence, autonomy, and relatedness are necessary for motivation to engage in healthy behaviors. Through medical specialty camps, these needs can be met by educating campers on how to manage T1D and realize they are not alone. The volunteer-based, five-day, inaugural tween–teen camp for youth with T1D was held on the campus of a university. The entire camp experience was engineered around the three basic needs described by the SDT. These needs were promoted by physical and educational activities and meeting friends. The Basic Psychological Needs and Frustration Scale was administered as a pre-, post-, and follow-up test. Two of the four measures were significant, the autonomy pretest (M = 3.93; SD = 0.75) to posttest (M = 4.49; SD = 0.56), with t(25) = −6.258; p ≤ 0.001) and relatedness pretest (M = 4.31; SD = 0.79) to posttest (M = 4.53; SD = 0.49), with t(25) = −2.168; p = 0.040; however, mean scores declined at the 3-month follow-up. Campers’ blood glucose levels were collected through an online platform that allowed staff to monitor blood glucose levels, with the week’s average being 150 mg/dL, and almost 71% remaining in the TIR. The results can be helpful for practitioners who want to use the SDT to structure and examine the effectiveness of medical specialty camps for youth with T1D.